Efforts To Improve Students' Learning Outcomes in Indonesian Language for Descriptive Text Material Using The "Guessing Style" Learning Method SDN 17 North Rantau Labuhan Batu - Sri Bunga; Sutikno; Rahmat Kartolo (International Journal of Educational Research Excellence (IJERE), 2026)
This study aims to determine the effect of the " Guess Style" learning method on students' learning outcomes in descriptive text material.The research questions in this study are:(1) Does the "Guess Style" learning method significantly affect students' learning outcomes in descriptive text material? (2) How significant is the difference in learning outcomes between students who use the " Guess Style" method and those who use conventional learning methods? This study was conducted at SDN 17 Rantau Utara, Labuhan Batu Regency, North Sumatra, during the 2025-2026 academic year. The results showed that before the treatment, the experimental class had an average pre-test score of 69.2, with a maximum score of 75 and a minimum score of 55, while the control class had an average pre-test score of 69.72, with a maximum score of 77 and a minimum score of 61. After the treatment, the experimental class's average post-test score increased to 80.2, with a maximum score of 95 and a minimum score of 70. Meanwhile, the control class obtained an average post-test score of 75.4, with a maximum score of 85 and a minimum score of 68. The percentage of students achieving the "Excellent" category (80-100) in the experimental class increased to 52%, while in the control class, it was only 24%. Hypothesis testing using a t-test showed that t_count = 2.668 was greater than t_table = 1.677 at a significance level of 0.05, leading to the rejection of H₀ and acceptance of Hₐ. This proves that the " Guess Style" method has a significant effect on improving students' learning outcomes compared to conventional methods. It can be concluded that the " Tebak Gaya" learning method is more effective in enhancing students' understanding of descriptive text material, as well as increasing students' active participation and interest in learning the Indonesian language